Difficult Journey from Delivery to Discharge, Case of Congenital Diaphragmatic Hernia - Karmacharya, RM; Dangol, S; Shrestha, M; Koju, R (Kathmandu University Medical Journal, 2015)
We report a case of congenital diaphragmatic hernia which was diagnosed prenatally for which surgical correction was done on second day of life. The child was discharged in 17 days and has resulted in good post repair condition of patient. Kathmandu University Medical Journal Vol.12(2) 2014: 149-150